Antigenotoxic properties of Paliurus spina-christi Mill fruits and their active compounds - Murat Zor; Sevtap Aydin; Nadide Deniz Güner; Nurşen Başaran; Arif Ahmet Başaran (BMC Complementary and Alternative Medicine, 2017)
Abstract Background Paliurus spina-christi Mill. (PS) fruits are widely used for different medical purposes in Turkey. Like in many medicinal herbs the studies concerning their activity, the activities of PS are also not well clarified. The aim of this study is to evaluate the antigenotoxicity of the compounds isolated and identified from the extracts of PS fruits. Methods The active compounds were separated, isolated, and determined by chromatographic methods and their structural elucidation was performed by Nuclear Magnetic Resonance (NMR) methods. The compounds were obtained from either ethyl acetate (EA) or n-butanol extracts. The cytotoxicities of the compounds using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and the antigenotoxic activities of the compounds using the alkaline single cell gel electrophoresis techniques (comet assay) were evaluated in Chinese hamster lung fibroblast (V79) cell lines. Results The isolated major compounds were identified as (+/−) catechins and gallocatechin from EA fraction and rutin from n-butanol fraction of PS fruits. Their chemical structures were identified by 1H-NMR, 13C-NMR, HMBC, and HMQC techniques. Half-maximal inhibitory concentration of catechins, gallocatechin, and rutin were found to be 734 μg/mL, 220 μg/mL, and 1004 μg/mL, respectively. The methanolic extract of PS (1-100 μg/mL) alone did not induce DNA single-strand breaks while catechins (1-100 μg/mL), gallocatechin (1-50 μg/mL), and rutin (1-50 μg/mL) significantly reduced H2O2-induced DNA damage. Conclusion It has been suggested that PS fruits and their compounds catechins, gallocatechin and rutin may have beneficial effects in oxidative DNA damage. It seems that PS fruits may be used in protection of the disorders related to DNA damage.